One Dimensional Ground Response analysis in Patan: Implications to Damage Pattern due to the 2015 Mw 7.8 Gorkha Earthquake - Niroula, Govinda Prasad; Chamlagain, Deepak; Acharya, Indra Prasad (Kathford Journal of Engineering and Management, 2023)
The 2015 Mw 7.8 Gorkha earthquake caused extensive damages in Kathmandu Valley located about 78 km SE from the epicenter. The damage patterns in the city clearly indicated the subsurface geology of the city had strongly modified the ground motion causing typical damages to tall structures. In this contribution, following one-dimensional approach, a ground response analysis is performed in Patan utilizing the deep borehole, shear wave profile and dynamic soil properties adopting both equivalent linear and non-linear approaches. The results of both equivalent linear and non-linear analyses were compared with the measured ground motions at soil site. It is found that the non-linear analysis better simulates the deamplification of the peak ground acceleration and strong shaking at longer period than the equivalent linear analysis. The obtained results confirm that the deamplification of PGA was due to the strong non-linear behavior of the fluvio-lacustrine deposits.